2018
DOI: 10.7717/peerj.4804
|View full text |Cite
|
Sign up to set email alerts
|

Potent antibacterial, antioxidant and toxic activities of extracts from Passiflora suberosa L. leaves

Abstract: Passiflora suberosa L. belonging to the family Passifloraceae is an important medicinal plant used in traditional medicinal system in Sri Lanka to treat diabetes, hypertension and skin diseases. We extracted P. suberosa leaves under reflux conditions using different solvents (hexane, chloroform, methanol and water), then subjected to phytochemical screening. Alkaloids, flavonoids and saponins and saponins and anthraquinones were present in hexane and chloroform extracts. Alkaloids, unsaturated sterols, triterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…The liver, renal, and cerebral toxicity of Devil's weed and the cytotoxicity of bitter oleander, guava, and passion fruit leaf extracts consumed by patients in our study are well described . It was interesting to note that the liver biopsies of those consuming Malabar nut tree (or vasaka) extracts demonstrated autoimmune hepatitis‐like histologic features, probably because of the presence of quinazoline alkaloids, phytosteroids, chalcones, triterpenoids, and flavonoids with possible immunomodulatory properties .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The liver, renal, and cerebral toxicity of Devil's weed and the cytotoxicity of bitter oleander, guava, and passion fruit leaf extracts consumed by patients in our study are well described . It was interesting to note that the liver biopsies of those consuming Malabar nut tree (or vasaka) extracts demonstrated autoimmune hepatitis‐like histologic features, probably because of the presence of quinazoline alkaloids, phytosteroids, chalcones, triterpenoids, and flavonoids with possible immunomodulatory properties .…”
Section: Discussionmentioning
confidence: 57%
“…(16,17) The liver, renal, and cerebral toxicity of Devil's weed and the cytotoxicity of bitter oleander, guava, and passion fruit leaf extracts consumed by patients in our study are well described. (18)(19)(20)(21) It was interesting to note that the liver biopsies of those consuming Malabar nut tree (or vasaka) extracts demonstrated autoimmune hepatitis-like histologic features, probably because of the presence of quinazoline alkaloids, phytosteroids, chalcones, triterpenoids, and flavonoids with possible immunomodulatory properties. (22) Hillman et al (23) showed that CAMinduced DILI is at least as severe in presentation as prescription medicine-related DILI, with higher rates of transplantation and lower transplant-free survival (17%) in those who progress to acute liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compound with potent antioxidant efficacy and thus capable of preventing generation of free radicals (Mpiana et al, 2013) could be used as an antisickling drug. Bandara et al (2018) revealed the presence of anthocyanin in the aqueous extract of Passiflora suberosa with potent antihaemolytic activity. Thus, antihaemolytic activity was found to be an important feature of antisickling agents.…”
Section: Phytochemical Screening Of the Plantsmentioning
confidence: 99%
“…Organic plant-based remedies are popular among Ayurveda and other modes of traditional medicine, as they are free of the harmful biproducts of conventional medicine [15]. At present, the focus on plants with a high polyphenolic content has increased due to their documented chemoprotective, antidiabetic, and anti-obesity potential [16], as well as the selective cell-killing ability [17] of such plants.…”
Section: Introductionmentioning
confidence: 99%